Prevalence of parasitic infection among diarrhetic patients attending the hospital in Ain Al-Tamur district, Karbala, Iraq - Ubaid, Moayad M. (Scientific Journal of Medical Research, 2022)
Introduction: Diarrhea is one of the most common diseases, and it causes death due to the depletion of body fluids, which leads to severe dehydration. The main causes of diarrhea are viruses, bacteria, and parasites. The most common parasites that cause diarrhea are “Entamoeba histolytica and Giardia lamblia.” Diarrhea infections are common in developing countries due to unhealthy environments, poor sewage drainage, and lack of attention to personal health. Methods: The study was conducted on patients suffering from diarrhea who visited the hospital in Ain Al-Tamur district, Karbala governorate, Iraq. The samples of stool were collected in a single-use container. At first, the stool sample was examined with the naked eye to detect the color and texture of stool, then using a microscope to detect the cysts of the parasites. Results: The results showed that the highest rate of parasitic infection was recorded for Entamoeba histolytica with an infection rate of (14%), while Giardia lamblia recorded the lowest rate of infection of (4%), and the differences were significant (p ? 0.05). Regarding the gender, the results revealed that the differences were not significant (p ? 0.05) between females and males for infection with both parasites. The study also showed the effect of a person’s age on infection rates. The highest infection rate of Entamoeba histolytica and Giardia lamblia was at the age of (16–45) years, while the minimum rate of infection was at (< 1 year). The results also show the effect of the different seasons of the year on the rates of Entamoeba histolytica and Giardia lamblia infection, as the results show the highest rate of Entamoeba histolytic infection was in the spring, while the lowest rate was in the summer. Regarding Giardia lamblia, the results revealed that the maximum infection rate was also in spring, but the lowest rate was in winter. Conclusion: We can conclude from the current study that the main causes of parasitic diarrhea in the Ain Al-Tamur district are Entamoeba histolytica and Giardia lamblia and the former is the more prevalent as well as the infection rates are affected by the age and seasonal variation but not affected by the gender.